Expression of immune checkpoints on circulating tumor cells in men with metastatic prostate cancer - Tian Zhang; Anika Agarwal; R. Garland Almquist; Daniella Runyambo; Sally Park; Elizabeth Bronson; Rengasamy Boominathan; Chandra Rao; Monika Anand; Taofik Oyekunle; Patrick Healy; Megan A. McNamara; et al. (BMC, 2021)
Abstract Background A subset of men with metastatic prostate cancer (mPC) responds to immune checkpoint inhibitors, and there is an unmet need to predict those most likely to benefit. We characterized circulating tumor cells (CTCs) for expression of immune checkpoint ligands in men with mPC as a non-invasive biomarker of immune evasion and immunotherapy benefit. Methods Three cohorts of patients were enrolled: 1) men with mCRPC starting abiraterone acetate/prednisone or enzalutamide (pre-ARSI), 2) men with mCRPC who were progressing on enzalutamide or abiraterone acetate/prednisone (post-ARSI), and 3) men with newly diagnosed metastatic hormone sensitive prostate cancer (mHSPC) starting androgen deprivation therapy. CTCs were captured using the CellSearch® system and stained for PD-L1, PD-L2, B7-H3, and CTLA-4 at baseline, on treatment, and disease progression. Summary statistics on mean CTCs per cohort, as well as rates of ligand positivity were used to analyze CTCs by cohort and by timepoint. Results Men in all cohorts and timepoints had prevalent CTC B7-H3 expression (> 80%). We found evidence for CTC PD-L1 expression across disease states, in which > 1 positive CTC or > 50% of CTCs were positive for PD-L1 in 40 and 30% of men with mHSPC, respectively, 60 and 20% of men with mCRPC pre-ARSI, and 70 and 30% of men with mCRPC post-ARSI. CTC PD-L2 expression was present in 20-40% of men in each disease state, while CTC CTLA-4 expression was rare, present in 20% of men with mCRPC pre-ARSI and 10% of men with mCRPC post-ARSI or with mHSPC. CTC immune checkpoint expression was heterogeneous within/between men and across disease states. Conclusions We have identified that CTCs from men with mPC heterogeneously express immune checkpoints B7-H3, PD-L1, PD-L2, and CTLA-4, and the detection of these immune checkpoints may enable monitoring on immunotherapy.